PHYSICAL CONFORMATION AND ULTRASONOGRAPHIC APPROACHES FOR BREEDING SOUNDNESS EVALUATION OF HIGH AND LOW LIBIDO CROSSBRED BULLS - KUMAR, A; SINGH, K; HONPARKHE, M; KAUR, S; GHUMAN, S P S; BRAR, P S (The Indian Journal of Animal Reproduction, 2016)
Physical conformation, scrotal circumference, testicular volume, rump fat thickness, testicular echogenecity andaccessory sex glands diameter in relation to libido (poor or high) in crossbred breeding bulls (n=22) was evaluated.Internal pelvic area (1121.60±42.19 vs 959.14±75.20 cm2) and testicular volume (454.30±21.51 cm3 vs 393.65±27.06cm3 ) were higher (p
Keywords: Breeding soundness; Crossbred bulls; Libido; Rump fat thickness; Ultrasonography